Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1001/archinte.163.22.2705
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Control

Abstract: Although overall BP control has improved, BP measurements still exceeded recommended levels in most patients. For patients with diabetes and renal disease BP was much better controlled in the more recent sample. However, BP control of patients with diabetes was similar to that of patients without diabetes, and not in agreement with the guideline-recommended tighter control. Thus, room for improvement remains, especially in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…These findings suggest that BP control improved significantly in RD patients in recent years, but only slightly in non-RD patients. A recent survey reported that RD patients had better BP control than non-RD patients (27); however, in that study 43% of RD patients had BP measurements of 140/90 mmHg or over, suggesting that the proportion of patients with controlled BP in the present study (62.7%) may be slightly higher than that seen in the previous study (57%) (27).…”
Section: Discussioncontrasting
confidence: 82%
“…These findings suggest that BP control improved significantly in RD patients in recent years, but only slightly in non-RD patients. A recent survey reported that RD patients had better BP control than non-RD patients (27); however, in that study 43% of RD patients had BP measurements of 140/90 mmHg or over, suggesting that the proportion of patients with controlled BP in the present study (62.7%) may be slightly higher than that seen in the previous study (57%) (27).…”
Section: Discussioncontrasting
confidence: 82%
“…Despite good evidence-based guidelines for best practice [22], routine clinical management, particularly of blood pressure, fails to achieve targets [23][24][25]. The challenge for management of the increasing numbers of patients with diabetes is how to deliver the level of risk reduction which is proven to reduce vascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…1113 A recently published systematic review and meta-analysis of large-scale randomized clinical trials demonstrated that effective BP lowering in patients with type 2 diabetes is associated with improved mortality and reduces the risk of micro- and macrovascular complications. 14 There is evidence of racial/ethnic and socioeconomic disparities in the prevalence and control of HTN 15,16 that have not been fully explored.…”
mentioning
confidence: 99%